THE IMPORTANCE OF VACCINATION OF HEPATITIS B IN CHILDREN (International Conference on Modern Science and Scientific Studies, 2025)
The first vaccine for active immunization, introduced in 1982, was prepared from purified, noninfectious 22-nm spherical forms of HBsAg derived from the plasma of healthy HBsAg carriers. In 1987, the plasma-derived vaccine was supplanted by a genetically engineered vaccine derived from recombinant yeast. The latter vaccine consists of HBsAg particles that are nonglycosylated but are otherwise indistinguishable from natural HBsAg. Current recommendations can be divided into those for preexposure and postexposure prophylaxis.